The Role of Business Courses and Collaboration Between Business Teams at The University on Entrepreneurial Intention - Puji Prabowo (Universitas Sebelas Maret, 2024)
This research focuses on business students, especially those who have attended business courses at universities and are active in collaboration programs for their businesses. Through the development of theoretical instruction and the provision of soft skills in entrepreneurship education, the aim is to offer a valuable experience for business students, enhancing their abilities and fostering their aspirations to become entrepreneurs. The main objective of this study is to explore the effect of business course integration and collaboration between businesses on their entrepreneurial intentions. The approach taken in this study is to use quantitative methods. This research was conducted on 205 business students in Bandung using the PLS-SEM (Partial Least Square - Structural Equation Model) method. The results of this study confirm the contribution of business courses with collaboration between business teams in entrepreneurship education, which contributes positively to developing interest in entrepreneurship among students. This research is useful for universities and schools that are carrying out entrepreneurship education for curriculum or program development.Keywords: business student, education, entrepreneurship, soft skills, university